Merawat Kemajemukan: Peran Pendidikan Agama Kristen dalam Menjaga Keharmonisan Antar Agama di Negeri Maneoratu - Lekatompessy, Rizky Rimona; Sopacua, Samel (MODERATE: Journal of Religious, Education, and Social, 2024)
Indonesian society is a pluralistic society. Living in diversity is a beauty but plurality can also be a problem. This article discusses the context of caring for pluralism through religious diversity in the State of Maneoratu amidst the many crises of religious tolerance in Indonesia. There is a harmonious coexistence style that is lived between individuals and even groups of people in the country of Maneoratu. Meneoratu is a country located in Telutih District, Central Maluku Regency, where members of the community consist of religious diversity, namely Islam and Christianity. In carrying out their daily social activities, these two religions live side by side with great respect for one another. This paper uses a descriptive qualitative method by collecting several data sources and analyzing data systematically. The results of the study state that the Maneoratu country has an awareness to respect religious diversity. However, it cannot be denied that there will be challenges in maintaining this diversity which is certainly influenced by various factors. For this reason, CRE which is the basis of education for every Christian in its implementation in families, schools, and churches must be able to transfer the values ​​of a strong awareness of tolerance among people.   Contribution: This article contributes significantly to understanding how the community in Maneoratu maintains religious diversity and fosters harmony among different faiths. Additionally, it highlights the role of Christian Religious Education (CRE) in fostering awareness of tolerance and unity within a pluralistic society.   Masyarakat Indonesia adalah masyarakat yang majemuk. Hidup dalam kemajemukan adalah sebuah keindahan, namun kemajemukan juga dapat menjadi suatu tantangan. Artikel ini membahas konteks perawatan kemajemukan melalui keragaman agama di Negeri Maneoratu di tengah krisis toleransi beragama yang terjadi di Indonesia. Di Negeri Maneoratu, terdapat gaya hidup harmonis yang dijalani oleh individu dan kelompok masyarakat, dengan anggota masyarakat yang terdiri dari keragaman agama, yaitu agama Islam dan Kristen. Negeri Maneoratu terletak di Kecamatan Telutih, Kabupaten Maluku Tengah, di mana kedua agama ini hidup berdampingan dengan sangat saling menghargai dalam kehidupan sosial sehari-hari. Penelitian ini menggunakan metode kualitatif deskriptif, dengan mengumpulkan berbagai sumber data dan menganalisis data secara sistematis. Hasil penelitian menunjukkan bahwa masyarakat di Negeri Maneoratu memiliki kesadaran untuk saling menghargai dalam keragaman agama. Namun, tantangan dalam merawat keragaman tersebut tetap ada dan dipengaruhi oleh berbagai faktor. Oleh karena itu, Pendidikan Agama Kristen (PAK), yang menjadi dasar pendidikan bagi umat Kristen, harus diterapkan di keluarga, sekolah, dan gereja, serta mampu mentransfer nilai-nilai kesadaran toleransi yang kuat antar umat.   Kontribusi: Artikel ini memberikan kontribusi penting dalam memahami bagaimana masyarakat di Negeri Maneoratu merawat keragaman agama dan menciptakan keharmonisan antar umat beragama. Selain itu, artikel ini juga menyoroti peran Pendidikan Agama Kristen (PAK) dalam membangun kesadaran toleransi dan kerukunan di tengah masyarakat yang majemuk.